Policing the Olympic gang: the rise and fall of the Portuguese Mafia - Fraser, Alistair (Policing and society, 2021)
Against a backdrop of rising youth violence in the UK, the issue of gang policing has once more risen to prominence. Intense debates surrounding police cuts have led to renewed calls for a ‘war on gangs’, echoing earlier responses to England’s summer of violent disorder in 2011. Drawing on a long-term ethnographic study of policing in the London Borough of Newham, this paper reports on a case-study of gang policing during a similarly fraught political moment. In the run-up to the 2012 London Olympics, a street-based group of minority ethnic youth – the so-called Portuguese Mafia (PGM) – became the primary focus for gang policing in the Borough. Though the group did not self-identify as a gang, their activities were inflated and became the subject of a targeted enforcement initiative. These distortions, we argue, resulted from the influence of political decision-making on the working practices of front-line police officers, amplified in a climate of austerity. Through the reconstruction of this ‘natural history’, we seek to contribute an empirical account of the ambiguities inherent in police definitions of gangs, and the discriminatory consequences of categorisation. Theoretically, the paper seeks to contribute a critical sociological account of gangs and gang policing that bridges extant objectivist and constructivist readings of gangs through engagement with the Bourdieusian concept of ‘field’.